Genome-Shuffling-Improved Acid Tolerance and Lactic Acid Production in Lactobacillus plantarum for Commercialization - LITA TRIRATNA; BUDI SAKSONO; LINDA SUKMARINI; ASEP SUPARMAN (Indonesian Society for microbiology, 2011)
We applied genome shuffling to improve the acid tolerance of Lactobacillus plantarum, while simultaneously enhancing lactic acid production. The starting populations were mutant libraries generated by gradual low pH adaptation and ultraviolet irradiation and then which were subjected to recursive protoplast fusion. A library of shuffled mutants (fusants) with genetic exchange is achieved by repetition of this process. After three rounds of genome shuffling, we obtained the best performing fusant that grow better at low pH 4.0 and consume glucose faster than does the wild type. In addition, lactic acid production of this fusant was 64% higher than that of the wild type. These results demonstrated that the genome shuffling has been successful in engineering L. plantarum with multiple beneficial improved phenotypes. In the future, this technology is a promising candidate to accelerate poorly characterized strains for commercialization